Laparoscopic distal pancreatectomy for benign or borderline malignant pancreatic tumors - Chung, Jun Chul; Kim, Hyung Chul; Song, Ok Pyung (Turkish Journal of Gastroenterology, 2014)
Abstract Background/Aims: Laparoscopic distal pancreatectomy (LDP) for benign conditions is increasingly performed. But, there are few limited studies about the outcomes of the laparoscopic surgery compared with open surgery. The aim of this study was to evaluate the clinical outcomes of LDP and compare it to that of open distal pancreatectomy (ODP). Materials and Methods: From July 2007 to February 2012, 60 consecutive patients (41 LDP patients and 19 ODP patients) who underwent elective distal pancreatectomy with an apparent diagnosis of benign or borderline malignant tumor were recruited into the current study. Results: There were no significant differences in operation time, transfusion, intravenous patient-controlled analgesia (IV-PCA) duration, pancreatic fistula, mortality, and recurrence between the two groups. Compared to ODP, LDP had lower blood loss (272.7±134.8 vs. 476.9±140.8 ml; p=0.002), shorter time to first flatus (2.4±0.5 vs. 4.0±1.5 days; p=0.003), earlier time to oral intake (3.4±1.6 vs. 5.4±1.9 days; p=0.013), and shorter postoperative hospital stay (9.4±6.9 vs. 17.0±6.7 days; p=0.043). Conclusion: LDP is a safe procedure and should be considered as a standard treatment option for benign or borderline malignant pancreatic tumors.